Retinitis Pigmentosa Treatment with Western Medicine and Traditional Chinese Medicine Therapies - Jian Xu; Qinghua Peng (Journal of Ophthalmology)
Current management of retinitis pigmentosa (RP) includes an attempt at slowing down the degenerative process through therapies that use either Western or traditional Chinese medicine (TCM). Novel therapies in Western medicine (WM) include use of tailor-made gene therapy, transplantation of stem cells, or neuroprotection treatment. TCM treatment includes two major approaches. These are orally applied herbal decoctions and acupuncture. In fact, all TCM treatments are based on the differentiation of a symptom-complex, which is the characteristic essence of TCM. Thus, diagnosed RP may be treated via the liver, the kidney, and the spleen. The principle behind these treatments is to invigorate the blood and brighten the eyes by toning up the liver and the kidney. Also treatments to cope with deficiencies in the two concepts that are unique and fundamental to TCM are considered: Qi or “vital energy” and Yin and Yang or the harmony of all the opposite elements and forces that make up existence. In particular, the Qi deficiency that results from blood stasis is addressed in these treatments. This paper also puts forward the existing problems and the prospect of the future development on integrating TCM with WM.